Is Economics Self-Correcting? Replications in the American Economic Review - Jörg Ankel-Peters; Nathan Fiala; Florian Neubauer (Institute for Replication (I4R), 2023)
This paper reviews the impact of replications published as comments in the American Economic Review between 2010 and 2020. We examine their citations and influence on the original papers' subsequent citations. Our results show that comments are barely cited, and they do not affect the original paper's citations - even if the comment diagnoses substantive problems. Furthermore, we conduct an opinion survey among replicators and authors and find that there often is no consensus on whether the original paper's contribution sustains. We conclude that the economics literature does not self-correct, and that robustness and replicability are hard to define in economics.
Keywords: A11; A14; B40; 330; replication; citations; meta-science